Functional disruption of cortical cingulate activity attenuates visceral hypersensitivity and anxiety induced by acute experimental colitis - Brenner, Lukas; Zerlin, Leah; Tan, Linette Liqi (Scientific reports, 2021)
Visceral pain is a highly complex experience and is the most common pathological feature in patients suffering from inflammatory gastrointestinal disorders. Whilst it is increasingly recognized that aberrant neural processing within the gut-brain axis plays a key role in development of neurological symptoms, the underlying mechanisms remain largely unknown. Here, we investigated the cortical activation patterns and effects of non-invasive chemogenetic suppression of cortical activity on visceral hypersensitivity and anxiety-related phenotypes in a well-characterized mouse model of acute colitis induced by dextran sulfate sodium (DSS). We found that within the widespread cortical network, the mid-cingulate cortex (MCC) was consistently highly activated in response to innocuous and noxious mechanical stimulation of the colon. Furthermore, during acute experimental colitis, impairing the activity of the MCC successfully alleviated visceral hypersensitivity, anxiety-like behaviors and visceromotor responses to colorectal distensions (CRDs) via downregulating the excitability of the posterior insula (PI), somatosensory and the rostral anterior cingulate cortices (rACC), but not the prefrontal or anterior insula cortices. These results provide a mechanistic insight into the central cortical circuits underlying painful visceral manifestations and implicate MCC plasticity as a putative target in cingulate-mediated therapies for bowel disorders.
Gesehen am 25.03.2021